The Impact of School Principals’ Managerial Competence and Customer Relationship Management on Educational Service Quality in Primary Schools - Sigit Rudiyanto; Widya Kusumaningsih; Nurkolis Nurkolis; Waewalee Waewchimplee (AL-ISHLAH: Jurnal Pendidikan, 2025)
Improving the quality of educational services is essential for ensuring institutional effectiveness and stakeholder satisfaction. However, few studies have explored the combined impact of school leadership and stakeholder engagement—particularly in primary education contexts. This study aims to examine the influence of school principals’ managerial skills and customer relationship management (CRM) on the quality of educational services in public elementary schools. A quantitative, correlational survey design was employed involving 97 teachers selected from a population of 128 through proportional random sampling. Data were collected using validated questionnaires and analyzed using descriptive statistics, prerequisite tests (normality, multicollinearity, heteroscedasticity, linearity), and hypothesis testing through simple and multiple linear regression. The results indicate that school principals' managerial skills significantly affect educational service quality, with a correlation coefficient (r) of 0.823 and an R² of 77.7%. Similarly, customer relations show a strong positive relationship with service quality (r = 0.857; R² = 73.4%). When combined, these two variables yield an even stronger influence (r = 0.866; R² = 75.0%). These findings highlight the critical role of effective leadership and stakeholder collaboration in enhancing educational services. Strengthening principals’ managerial competencies and implementing CRM-oriented practices can lead to better communication, trust, and responsiveness in schools. This study offers practical implications for policymakers and school leaders to design targeted professional development and engagement strategies that support sustainable educational improvement.